Resveratrol Treatment of Mice With Pressure-Overload–Induced Heart Failure Improves Diastolic Function and Cardiac Energy Metabolism. (January 2015) - Sung, Miranda M.; Das, Subhash K.; Levasseur, Jody; Byrne, Nikole J.; Fung, David; Kim, Ty T.; Masson, Grant; Boisvenue, Jamie; Soltys, Carrie-Lynn; Oudit, Gavin Y.; Dyck, Jason R.B.
<x xml:space="preserve">Abstract</x> Background— Although resveratrol has multiple beneficial cardiovascular effects, whether resveratrol can be used for the treatment and management of heart failure (HF) remains unclear. In the current study, we determined whether resveratrol treatment of mice with established HF could lessen the detrimental phenotype associated with pressure-overload–induced HF and identified physiological and molecular mechanisms contributing to this. Methods and Results— C57Bl/6 mice were subjected to either sham or transverse aortic constriction surgery to induce HF. Three weeks post surgery, a cohort of mice with established HF (% ejection fraction <45) was administered resveratrol (≈320 mg/kg per day). Despite a lack of improvement in ejection fraction, resveratrol treatment significantly increased median survival of mice with HF, lessened cardiac fibrosis, reduced gene expression of several disease markers for hypertrophy and extracellular matrix remodeling that were upregulated in HF, promoted beneficial remodeling, and improved diastolic function. Resveratrol treatment of mice with established HF also restored the levels of mitochondrial oxidative phosphorylation complexes, restored cardiac AMP-activated protein kinase activation, and improved myocardial insulin sensitivity to promote glucose metabolism and significantly improved myocardial energetic status. Finally, noncardiac symptoms of HF, such as peripheral insulin sensitivity, vascular function, and physical activity, were improved with resveratrol treatment. Conclusions— Resveratrol treatment of mice with established HF lessens the severity of the HF phenotype by lessening cardiac fibrosis, improving molecular and structural remodeling of the heart, and enhancing diastolic function, vascular function, and energy metabolism.